Case Report: A prenatal diagnosis of osteogenesis imperfecta in a patient with a novel pathogenic variant in COL1A2 - Pelaez-Chomba, MS (2023)
Osteogenesis imperfecta is considered a rare genetic condition which is characterized by bone fragility. In 85% of cases, it is caused by mutations in COL1A1 and COL1A2 genes which are essential to produce type I collagen. We report the case of a female neonate delivered to a 27-year-old women at San Bartolomé Teaching Hospital with a family history of clavicle fracture. A prenatal control with ultrasound was performed to the mother at 29 weeks. A fetus with altered morphology and multiple fractures was found. Therefore, a prenatal diagnosis of osteogenesis imperfecta was performed. The neonate was born with a respiratory distress syndrome and an acyanotic congenital heart disease. Therefore, she remained in NICU until her death. We highlight the importance of prenatal diagnosis, genetic counseling and a multidisciplinary evaluation in this type of pathologies and report a new probably pathogenic variant in the COL1A2 gene detected by exomic sequencing in amniotic fluid.